An unusual source of electromagnetic interference. Issue 10 (16th July 2018) - Verma, Kunal Pradip; Adam, David
Abstract: A 62‐year‐old male presented to his treating cardiologist for routine interrogation of his implantable cardiac defibrillator on the background of severe ischemic cardiomyopathy and end‐stage kidney disease on hemodialysis. The device log revealed multiple paroxysms of atrial fibrillation; however, upon scrutinizing these episodes it was evident that they always corresponded to episodes of hemodialysis while dialyzing through a chronic dialysis catheter, but not while dialyzing via an arteriovenous fistula. We report the novel finding of inappropriate sensing of current leak from the catheter by a lead with a floating atrial dipole.